ISLAMIC THEOLOGICAL THOUGHT IN INDONESIA AND ITS IMPLICATIONS FOR EDUCATION - Nurseri Hasnah Nasution (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
The very dynamic development of the world and the increasingly sophisticated advances in science and technology coupled with the emergence of various problems in society have led to a reconstruction of theological themes. In addition, in the decade of the 70s, enthusiasm for theological thought emerged in Indonesia. The excitement is a response to the problems of Muslims. In the 20th century, this enthusiasm was increasingly complex due to the return of Indonesian theologians who had studied in the West. They caused a paradigm shift among Indonesian Muslims, giving rise to a variety of religious articulations covering the levels of thought, understanding, appreciation, and social systems. This diversity causes vulnerability in the internal environment of religious communities in relation to wider life such as economics, politics, ideology, science, technology, and education. This phenomenon causes the main themes of Islamic theology in Indonesia to experience very dynamic dynamics and have implications for education in Indonesia. Therefore, research on this phenomenon is very significant. The purpose of this study is to find out the implications of Islamic theological thinking for thought (a comparative study in the pre-independence and post-independence periods), find patterns of Islamic theological thought in Indonesia, and its influence on Indonesian Islamic education. To find this goal, this study uses a rationalistic qualitative research approach. This research is a type of development research and uses literature and documentation to collect data, hermeneutics to analyze data. The results of this study are that the main themes of Islamic theology in Indonesia experience dynamic dynamics. The dynamics can be seen in the tendency of orientation from theocentric to anthropocentric. Islamic theology, which originally defended God (theocentric) and is now in favor of humanity (anthropocentric), is transformative, liberating, and departs from human revolution. Islamic theology emerges as a reaction to empirical and theoretical realities that have implications for education.